1983
DOI: 10.1084/jem.157.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of fetal hematopoietic cells that express the common acute lymphoblastic leukemia antigen (CALLA).

Abstract: Fetal hematopoietic cells that express the common acute lymphoblastic leukemia antigen (CALLA) were purified from both fetal liver and fetal bone marrow by immune rosetting with sheep erythrocytes coated with rabbit anti-mouse immunoglobulin and by fluorescence-activated cell sorting. Dual fluorescence techniques disclosed that these cells were heterogenous with respect to the expression of a series of differentiation and activation antigens defined by monoclonal antibodies. Thus, whereas all CALLA+ cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…CALLA is present on hemopoietic precursors found in bone marrow and fetal liver, but not on mature B cells (9,44). The demonstration ofthe identity ofCALLA and NEP implies that this enzyme is associated with early stages in B cell ontogeny (9,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CALLA is present on hemopoietic precursors found in bone marrow and fetal liver, but not on mature B cells (9,44). The demonstration ofthe identity ofCALLA and NEP implies that this enzyme is associated with early stages in B cell ontogeny (9,44).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration ofthe identity ofCALLA and NEP implies that this enzyme is associated with early stages in B cell ontogeny (9,44). This might be linked to the production of a specific peptide whose expression is transiently needed in maturation, possibly by hydrolysis of a precursor molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies indicated that CALLA was also expressed by certain other lymphoid malignancies with an immature phenotype (3) and by early lymphoid progenitors from fetal liver, fetal and adult bone marrow, and thymus (3)(4)(5)(6)(7). These CALLA' cells have the phenotypic characteristics of cells that are either uncommitted to B-or T-cell lineage or committed to only the earliest stages of B-cell differentiation.…”
mentioning
confidence: 99%
“…These cells lack a number of other B cell markers such as Y29/55 [16], RFB-6, or show only cytoplasmic, but no membrane expression of RFB-4 or To15. The phenotypic features of these Tdr+ cells are similar to the blast cells seen in common acute lymphoblastic (cALL) and pre-B ALL [9,11,[15][16][17].…”
Section: Malignant B Cellsmentioning
confidence: 90%
“…TdT+ cells are present in large proportions amongst the lymphoid cells of fetal liver [11,15] and fetal BM [13,15]. These cells lack a number of other B cell markers such as Y29/55 [16], RFB-6, or show only cytoplasmic, but no membrane expression of RFB-4 or To15.…”
Section: Malignant B Cellsmentioning
confidence: 99%